Antara Kaya dan Hina dalam Prespektif Filsafat Ekonomi Islam: Posisi Harta dalam Pembelajaran Hidup (Perspektif Pendidikan Islam) - Musfiqoh, Siti (Didaktika Religia, 2016)
Experts agree that the theory and practice of education should be based on thebasic conception of human beings, including the economic role therein. Educationis a symptom and human needs. In the sense that if someone does not get aneducation, then they will not be a real human being and will not be able to fulfillits function as a human being useful in life and living. The final goal of the HumanEssence in Islamic education is to create men in the concept of a perfect Moslemal-insan al-kamil, the man who always constancy and skilled in the functioningcontinuum of physical and their spiritual power to always be submissive andobedient to the holy God Almighty.